Heat-treated palm oil fuel ash as an effective supplementary cementitious material originating from agriculture waste - Alsubari, Belal; Shafigh, Payam; Ibrahim, Zainah; Jumaat, Mohd Zamin (Elsevier, 2018)
Palm oil fuel ash (POFA) is generated from the combustion of oil palm waste. This ash is considered a disturbance to the environment since it is dumped without being profit return or recycled, thus causing environmental problems and human health hazards. However, it has been proven that POFA is a pozzolanic material that can be utilized as cement replacement in concrete. If POFA is heated at high temperature, it exhibits better pozzolanic performance. In this study, the treatment processes as well as microstructure and pozzolanic characteristics of POFA are considered. Ordinary Portland cement was replaced with 0, 30, 50, and 70% treated POFA (T-POFA) in a paste. The hydration products of different hardened pastes were checked by means of simultaneous thermal analysis (STA), X-ray diffraction (XRD), and field emission scanning electron microscopy (FESEM) in order to assess the effect of TPOFA on the paste microstructure. According to the test results, the physical properties and chemical composition of T-POFA greatly enhanced due to heat treatment and the milling process. It was observed that the calcium hydroxide content decreased in pastes containing T-POFA upon hardening, which is evidence of its consumption by the pozzolanic reaction. The FESEM images displayed needle-like and reticular C–S–H phases in the control paste, while floc-like and fibrous-like C–S–H phases well-connected to each other were observed in the pastes containing T-POFA.